2001
DOI: 10.1523/jneurosci.21-17-06905.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding Mechanisms Underlying Perceived Roughness of Finely Textured Surfaces

Abstract: Combined psychophysical and neurophysiological studies have shown that the perceived roughness of surfaces with element spacings of >1 mm is based on spatial variation in the firing rates of slowly adapting type 1 (SA1) afferents (mean absolute difference in firing rates between SA1 afferents with receptive fields separated by approximately 2 mm). The question addressed here is whether this mechanism accounts for the perceived roughness of surfaces with element spacings of <1 mm. Twenty triangular and trapezoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(120 citation statements)
references
References 32 publications
9
111
0
Order By: Relevance
“…psychophysics | somatosensory cortex | vibration | whisker | finger A n effective approach to uncover how neuronal activity leads to sensation is to vary stimulation parameters while correlating changes in firing with changes in the percept (1)(2)(3)(4)(5). In the present work, we measured changes in neuronal activity in rat somatosensory ("barrel") cortex induced by variation in vibration parameters and correlated these changes with perceptual reports from human subjects.…”
mentioning
confidence: 96%
“…psychophysics | somatosensory cortex | vibration | whisker | finger A n effective approach to uncover how neuronal activity leads to sensation is to vary stimulation parameters while correlating changes in firing with changes in the percept (1)(2)(3)(4)(5). In the present work, we measured changes in neuronal activity in rat somatosensory ("barrel") cortex induced by variation in vibration parameters and correlated these changes with perceptual reports from human subjects.…”
mentioning
confidence: 96%
“…The findings of Lederman and Taylor [13] and Yoshioka et al [14] show that the haptic perception of roughness depends mainly on the groove width and ridge width, therefore these were individually varies. For the structure of the geometric surfaces, lines and diamond shapes were chosen (see Table1) because their shapes are typical for leather surfaces.…”
Section: -P2mentioning
confidence: 96%
“…The result of their studies was, that the same neural mechanism accounts the perceived roughness weather is a fine or a coarse surface. [14] In summary of all of those studies there is no method that sufficiently relates human perception of roughness to physical parameters of the materials. In order to achieve a proper method, descriptors had to be found that are the most meaningful for the characterization.…”
Section: State Of Researchmentioning
confidence: 99%
“…The rotating drum has been used to scan various types of raised patterns across the glabrous skin of both monkeys (Connor et al, 1990;Connor and Johnson, 1992;Blake et al, 1997;DiCarlo et al, 1998;DiCarlo and Johnson, 1999Yoshioka et al, 2001), in neurophysiological experiments, and humans in psychophysical and percutaneous recording experiments (Phillips et al, 1992). Stimuli such as raised letters and textured surfaces are mounted on a drum; the drum is brought in contact with the skin and rotated.…”
Section: Previous Devicesmentioning
confidence: 99%
“…By moving the drum in small increments laterally, a spatial pattern can be moved across the fingerpad while single-unit recordings are made. Recordings of both peripheral (Connor et al, 1990;Connor and Johnson, 1992;Blake et al, 1997;Yoshioka et al, 2001) and central DiCarlo et al, 1998;Johnson, 1999, 2002) neurons have been made with this device. The same spatial patterns can be presented to human observers in psychophysical tasks in which they are asked to identify the patterns.…”
Section: Previous Devicesmentioning
confidence: 99%